Islamic Thought of Sheikh Nawawi al-Bantani and His Contribution to Developing Islamic Education - Kusbiantoro, Handaru; Syafiq, Ahmad; Prasetyo, Dony Agus; Setyawati, Hidayati Rina; Khoir, Mulyanto Abdul (STIT Ahlussunnah Bukittinggi, 2025)
This study examines the Islamic thought of Sheikh Nawawi al-Bantani and his contribution to Islamic education in the Indonesian archipelago. The method used is qualitative with a literature study approach, analyzing Sheikh Nawawi's original works as well as secondary literature related to his biography, intellectual network, and influence on Islamic education. The results of the study show that Sheikh Nawawi developed more than a hundred works in the fields of interpretation, fiqh, Sufism, tawhid, and morals, emphasizing the integration of sharia, Sufism, and morals as the foundation of holistic education. His thoughts formed a paradigm of Islamic education that is moderate, integrative, and adaptive to the challenges of modernity and globalization. This study affirms the relevance of Sheikh Nawawi's thoughts as a conceptual reference for contemporary Islamic education, strengthening the character of the ummah, and developing Islamic scholarly traditions.